Harmonic Phase Shifter for Discrete Amplitude Modulation Technique - Mahmood, Anas Lateef; Lazim, Mohammed Tofik (Nahrain University College of Engineering Journal, 2010)
In discrete amplitude modulation or integral-cycle control, subharmonic and higher order harmonic components are generated in the three phases of a three phase system. These harmonic components are found to be unbalanced in phase displacement. The correction of the unbalanced phase displacement angles of a particular subharmonic or higher order harmonic for this type of triggering is investigated to solve the limitation of use of this important type ofcontrol as a drive and many other industrial applications. The multiple of 2 phase shifting technique is used to correct unbalanced phase displacement angles produced in a three-phase system. A computer-based harmonic phase corrector is designed and tested with threephase resistive and induction motor loads. It isfound that there is a well agreement between the theoretical and experimental results and it is believed that the major problems associated with the integral-cycle triggering mode with three-phase ci